Run on your new legs. 5 - Midori, Wataru (Yen Press, 2023)
"As schools reopen and clubs reconvene after COVID-19 closures, Kikuzato is eager to try out his new leg. But even with the improved fit, his worry about falling like he did in his first public race plagues his training for the next. Running is as much a mental game as it is a physical one, and between his fear and his fight with Take, Kikuzato isn't seeing the improvement he hoped his new leg would bring. If he means to succeed, Kikuzato must answer one question for himself: 'Why am I running anyway?'"--Page [4] of cover.